Source rock geochemistry and liquid and solid petroleum occurrences of the Ouachita Mountains, Oklahoma. - Curiale, Joseph Anthony (My University, 1981)
Several stratigraphic intervals in the Ouachita Mountains possess adequate source potential for petroleum generation, based on contents of total organic carbon and extractable organic matter. Mississippian/Devonian rocks are probably gas-generative, while pre-Devonian rocks are oil-generative. The entire Paleozoic section examined is thermally mature enough to have generated oil, being located at about the middle of the oil window. In general, the best oil source potential is present in upper Ordovician (Polk Creek/Womble) rocks.

Crude oils, solid bitumens and potential oil source rocks of the Frontal and Central Ouachita Mountains of southeastern Oklahoma are examined. The purposes of this study are to characterize the organic matter in each of these materials, and to correlate oils to potential source rocks in the Ouachita Mountains.

Oil-source rock correlation techniques indicate that oils examined from the Frontal and Central Ouachita Mountains have a Siluro-Ordovician (Missouri Mountain-Polk Creek-Womble) source. This conclusion is supported by n-alkane, sterane and isotope ratio data. Listric reverse faults in the Frontal Ouachitas are proposed as migration conduits, connecting Siluro-Ordovician source rocks with Carboniferous reservoir rocks. A model is proposed whereby upward migrating oil is gradually degraded as it nears the surface, yielding the near-surface solid bitumen deposits. Further development of this model suggests that significant quantities of oil are yet to be discovered.

Four Ouachita Mountain oils and seven solid bitumens (grahamite and impsonite) are analyzed. The oils are paraffinic and range from 31.8 to 43.1 API gravity. Results indicate that the oils are thermally mature and generally unaltered. All four oils are commonly sourced, as suggested by n-alkane, sterane and hopane distributions, stable isotope ratios, infrared spectra and vanadium/nickel ratios. A common source for the solid bitumens is also suggested by isotope ratios and pyrolyzate characteristics. An origin due to crude oil biodegradation is suggested for these soilds, based on carbon isotope ratios, elemental analyses, and sterane distributions of the solid bitumen pyrolyzates.
Keywords: Geochemistry.